Envelope [from Joseph Mary Plunkett], addressed to Grace Gifford - Plunkett, Joseph Mary, 1887-1916; Plunkett, Grace Gifford, 1888-1955 (1915)
Envelope addressed to: "Miss Grace Gifford / 8 Temple Villas / Palmerston Rd. / Rathmines / Dublin".
Keywords: Plunkett, Joseph Mary, -- 1887-1916 -- Correspondence; Plunkett, Grace Gifford, -- 1888-1955 -- Correspondence